(untitled) (Journal of actual problems of jurisprudence, 2018)
The article considers both the importance and the complexity of the conceptual category «inner conviction», and the author proposes that the legislator disclose the content of this concept. The treatment of inner conviction in the legal literature is very diverse, not always harmless and highly controversial. Moreover, it seems to us that the internal conviction of the subjects specified in the articles of the Criminal Procedure Code of the Republic of Kazakhstan may vary significantly, reflecting the specific procedural position of each of the subjects (judge, investigator, prosecutor, investigator, jurors), despite the fact that each subject is concerned with the evaluation of evidence by this subject. Key words: criminal justice, evaluation of evidence, internal conviction, subject of evidence evaluation, prosecutor.